The Influence of Environmental Quality on Life-History Strategies and the Development of Perfectionism - Park, Si Hyun; Kim, Jaehee; Cho, Kayleen; Kim, Aiden (Technium Social Sciences Journal, 2025)
This paper investigates the following research question: “How do harsh and safe environments shape life-history strategies, and how do these strategies affect the development of perfectionism?”. Driven by our interests in evolutionary psychology, we wanted to explore the effects of environmental quality on life-history strategies, and thus the influence of life-history strategies on perfectionism. Our study aligns with our hypothesis that individuals raised in safe, stable, and resource-rich environments would adopt slower life-history strategies, leading to higher levels of perfectionistic traits, and that individuals raised in unpredictable, unstable, and resource-scarce environments would adopt fast life-history strategies, leading to lower levels of perfectionistic traits. Our findings suggest that perfectionism may reflect an evolved psychological strategy shaped by early environmental conditions (byproduct of the secure and affluent environment), rather than being a fixed personality trait.